New Composition Concept for Keroncong Music in the Oboe Concerto with Keroncong and Orchestra - Singgih Sanjaya (IJCAS (International Journal of Creative and Arts Studies), 2018)
this research aims to design a new concept in keroncong music creation with an explorative method. Keroncong is one kind of entertainment musics in indonesia that has a long existece and evolved up to today. Keroncong music is a musical mixture of a western diatonic music with Javanese gamelan music. the term of keroncong comes from the sound “...crong crong crong...” on the ukulele instrument that played rasquardo. an instrumentation music consists of: vocals, violin, flute, cak, cuk, cello, guitar, and bass. during this moment, keroncong is basically just served as a vocal accompaniment music. this becomes a driving force for the author to compose a special composition for keroncong music solo instrument. there is a new concept used in the arranging of this composition, as follows. this composition is designing a concerto, which is a type of the instrumental musics with a western diatonic instrument on the part-one of the solo oboe and an English horn in part-two, with keroncong music and orchestra. the conclusion of these designs are as follows. Keroncong music will be able to stand on its own as an instrumental music.